2007
DOI: 10.3748/wjg.v13.i31.4255
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effect of Epigallocatechin-3-gallate on the human gastric cancer cell line MKN45viaactivation of the mitochondrial pathway

Abstract: These data support that EGCG can induce apoptosis of the human gastric cancer cell line MKN45, and the effect is in a time- and dose-dependent manner. The apoptotic pathway triggered by EGCG in MKN45 is mitochondrial-dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…miR-16 may mediate the EGCG induction of apoptosis by targeting Bcl-2. EGCG was shown to induce apoptosis and also suppress Bcl-2 in different cell lines [19,20,32,33]. In addition to apoptosis induction, treatment of HepG2 cells with EGCG induced miR-16 and also down-regulated the expression of its target gene Bcl-2.…”
Section: Discussionmentioning
confidence: 98%
“…miR-16 may mediate the EGCG induction of apoptosis by targeting Bcl-2. EGCG was shown to induce apoptosis and also suppress Bcl-2 in different cell lines [19,20,32,33]. In addition to apoptosis induction, treatment of HepG2 cells with EGCG induced miR-16 and also down-regulated the expression of its target gene Bcl-2.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies also revealed the effects of (−)-EGCG on gastric cancer [63,64]. The apoptotic effect of (−)-EGCG on the human gastric cancer cell line MKN45 was observed via activation of the mitochondrial pathway [63]. …”
Section: In Vitro and In Vivo Preclinical Studies On Tea Polyphenolsmentioning
confidence: 99%
“…EGCG, the major constituent in the tea, has been shown to have an inhibitory effect on gastrointestinal carcinogenesis in several studies 16–18 . In our previous study we demonstrated that EGCG could inhibit the growth of different digestive tumor cells 19 and EGCG can induce the mitochondrial‐dependent apoptotic pathway in the MKN45 cell line 20 . An experimental study suggests there is an inverse association between the risk of colon cancer and habitual tea consumption in the USA 21 .…”
Section: Discussionmentioning
confidence: 93%
“…[16][17][18] In our previous study we demonstrated that EGCG could inhibit the growth of different digestive tumor cells 19 and EGCG can induce the mitochondrial-dependent apoptotic pathway in the MKN45 cell line. 20 An experimental study suggests there is an inverse association between the risk of colon cancer and habitual tea consumption in the USA. 21 A population-based, case-control study of esophageal cancer in urban Shanghai suggests that green tea consumption has a protective effect.…”
Section: Discussionmentioning
confidence: 99%